Understanding the context of informality: urban planning under different land tenure systems in Mzuzu city, Malawi - Manda, Mtafu Almiton Zeleza Chinguwa (School of Architecture, Planning and Geomatics, 2020)
A key feature of urbanisation in African and many other Global South cities is the prevalence and persistence of urban informal settlements. Despite planning attempts and claims to directly address and contain informal settlements, informality nonetheless continues to be the dominant form of shelter. However, there is insufficient understanding of how and why informality persists in the African urban context and why urban planning seems unable to engage with this aspect of urban growth and change. This situation also prevails in Malawian cities. This study sought to explore and understand the role of state-society engagements in the production and proliferation of housing informality in Mzuzu City. The thesis is informed by a recognition that planning theory has predominantly relied on Global North (Western) ideologies such as Habermesian inspired collaborative and communicative planning approaches which argue that consensus can realise planning goals and visions. The appeal, and hence adoption and application of these approaches in the Global South have largely failed to deliver the kind of planning outcomes seen in the Global North for many reasons, including the different political power dynamics and colonial historical contexts within which planning operates. The state-society engagements in the Global South contexts show that the state, rather than regulating development, is implicated in the production of informality in ways similar to those of inhabitants. These contexts point to the need to develop planning concepts which have a better relevance in rapidly growing and under-resourced urban settlements in the Global South. The thesis contributes to an emerging body of knowledge that has come to be called the Global South Planning Theory Project. The scholars promoting this project argue for the importance of context in planning theory development and in this case the need to consider the contribution of the Global South to planning and understanding of the urbanisation processes. In this regard, the thesis draws on various Global South concepts such as informality as a mode of urbanisation (Roy, 2009), gray spaces (Yiftachel, 2009), conflicting rationalities (Watson 2003), quiet encroachment (Bayat, 2010), insurgency (Holston, 2008) and hidden transcripts (Scott,1990) to frame the analysis of housing informality in Mzuzu City. The case study method (Yin 2014) was used to collect and analyse data from three informal settlements of Luwinga, Salisburyline and Geisha each having developed on land of a specific tenure: customary, public and private, respectively. Interviews and discussions were held with state officials, chiefs, block leaders, clan leaders, and senior citizens as well as groups of inhabitants in form of focus group discussions. Observations, literature review and archival data supplemented the information from the interviews and discussions. The analysis of the results indicates that state-society engagement in the informal settlements is about the application of the various strategies by each side in seeking to either achieve planned orderly urban growth or the right to land and life in the city. The study also shows that these strategies manifest, from the perspective of the state, through several laws, policies, regulations, and an assortment of practices that the planning system uses as a tool of the state. Among the state strategies are threats of evictions, demolitions and organising citizens to participate in development committees. However, when the state utilises these strategies, it is not always for the achievement of planned orderly urban growth as professed, but on many occasions for revenue generation through property taxation, for land control, for vote-gaining or for personal gain. On the other hand, inhabitants use threats of court action, violence, collaboration with state actors, hidden transcripts (Scott, 1990), spatial protests ( Yakobi, 2004) and quiet encroachment (Bayat, 2010) to achieve their objectives to retain their land rights, to provide their basic need of shelter and to stay in the city. The inhabitants seeking survival strategies were also found not immune to the clientelist ambitions of local politicians. The study noted the shifting state discourses of informal settlements from a view of them as utter illegality to gradual political acceptance or regularisation of their existence. Finally, the study found many aspects of rationality conflicts, which either occurred between the state and society directly, among state actors, among citizen actors and across the two spheres. Within the state, ethical conflicts in which state officials deliberately frustrated the visioning of planned orderly urban growth were found to be rampant. State-society engagements therefore can be said to be a contributor to housing informality. In the case of Mzuzu, these engagements occur in multiple settlements regardless of land tenure situation. These engagements suggest that rationality conflicts occur within multi-layered settings, across state-society spheres as well as beyond specific project interventions implemented within single settlements.